KELOMPOK ETNIS DALAM PELUKAN ELITE LOKAL (Studi Tentang Politik Etnis Dalam Pemilukada Kota Ternate Tahun 2010) - , Irmon Machmud, SIP ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study emphasized ethnic politics, namely how ethnic instrumentation (commodification) in electoral arena, specifically in local election 2010 in Ternate City. In other word, ethnic or ethnicity has become âmerchandiseâ or being capitalized by local elites in effort to seize resources of power. It is highly argued that ethnic become important instrumentation in the arena of local political contestation. This research has using analytic descriptive design, qualitative approach as well as referred to both primary and secondary data. While, the data got from field observation, indepth interview to informants who have relevant competence or tightly related to the research problem, and also documentation. Theoretically, the ethnic just become instrumentation of local elites or in refer to Marxian term, ethnic just become commodity (commodificated). This research has shown that ethnic instrumentation (commodification) by local elites in political arena, like in local election 2010 in Ternate city, it has shown from commence of candidacy for mayor and vice mayor of Ternate city who are cutting off ethnicity by political party and independent candidate. The ethnic cross-cutting or combination is obvious in the candidate pairs: Ikbal-Vaya (Sanana-Makian), Sidik-Saiful (Ternate-Makian), Burhan-Arifin (Tidore-Ternate), and Wahda-Hidayat (Makian-Ternate). The combination of candidate based on ethnicity has not only used by parties but also âcombined as wellâ by power of outside party, such as sultanate of Ternate and Tidore, as well as two formal rulers, they are Mayor of Ternate city and Governor of North Maluku. Another findings has shown ethnic instrumentation also visible from how was the pattern of elite approach (the candidates) toward ethnic groups. This matter could be seen from several social activities such as barifola (cut open of house), Legu Gam (people party), and investment in education field for certain ethnics. The candidates have together seizing or establishing or managing directly ethnic organizations to obtain political support from elements of ethnic. Instrumentation (commodification) of other ethnics has visible from how the elites produced ethnic issues or discourses in efforts to make instant mobilization of ethnic mass. Based on the above research findings, so it is could be concluded that ethnic or ethnicity has become instrumentation and commodity by local elites in the arena of electoral politics (local election). The ethnic has been commodificated in such a manner as described in the above findings to gain victory in the local political contestation for seizing of political resources. This research is expected to make contribution of knowledge in the field of political science and practically gives outstanding lessons about how local elites have treated ethnic groups/ethnicity, and also not just become commodity that being sold in political arena.